2022
DOI: 10.3389/fphys.2022.1047324
|View full text |Cite
|
Sign up to set email alerts
|

A review of the bioeffects of low-intensity focused ultrasound and the benefits of a cellular approach

Abstract: This review article highlights the historical developments and current state of knowledge of an important neuromodulation technology: low-intensity focused ultrasound. Because compelling studies have shown that focused ultrasound can modulate neuronal activity non-invasively, especially in deep brain structures with high spatial specificity, there has been a renewed interest in attempting to understand the specific bioeffects of focused ultrasound at the cellular level. Such information is needed to facilitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 188 publications
0
2
0
Order By: Relevance
“…This trade-off explains why high-frequency and low-frequency FUS are typically used for superficial and deep tissue imaging, respectively. In addition to imaging, accumulating reports have shown that low-intensity FUS (averaging < 100 W/cm 2 acoustic pressure over the pulse train) can induce a wide range of bio-effects, including heating, mechanical forces, and cavitation (Figure 1) (Collins and Mesce, 2022). While the thermal effect is known to be triggered by continuous FUS at high frequencies (Pinton et al, 2010;Rossmanna and Haemmerich, 2014), the parameters of FUS that specifically cause other bio-effects are not fully understood (Chu et al, 2022).…”
Section: Ultrasound and Sonogeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…This trade-off explains why high-frequency and low-frequency FUS are typically used for superficial and deep tissue imaging, respectively. In addition to imaging, accumulating reports have shown that low-intensity FUS (averaging < 100 W/cm 2 acoustic pressure over the pulse train) can induce a wide range of bio-effects, including heating, mechanical forces, and cavitation (Figure 1) (Collins and Mesce, 2022). While the thermal effect is known to be triggered by continuous FUS at high frequencies (Pinton et al, 2010;Rossmanna and Haemmerich, 2014), the parameters of FUS that specifically cause other bio-effects are not fully understood (Chu et al, 2022).…”
Section: Ultrasound and Sonogeneticsmentioning
confidence: 99%
“…Although many efforts have been made to evaluate the correlation between FUS parameters and induced bio-effects (Collins and Mesce, 2022), most of them focus on only one type of tissue or cell. Tissues with different acoustic properties could exhibit distinct bio-effects upon FUS stimulation.…”
Section: Conclusion Challenges and Perspectivesmentioning
confidence: 99%